2004
DOI: 10.1037/0882-7974.19.1.125
|View full text |Cite
|
Sign up to set email alerts
|

Aging: A Switch From Automatic to Controlled Processing of Sounds?

Abstract: In this article, the authors show that aging differentially affects peoples' ability to automatically and voluntarily process auditory information. Young, middle-aged, and older adults matched behaviorally in an auditory discrimination task showed similar patterns of neural activity indexing the voluntary and conscious detection of deviant (i.e., target) stimuli. In contrast, a negative wave indexing automatic processing (the mismatch negativity) was elicited only in young adults for near-threshold stimuli. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
88
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 36 publications
10
88
1
Order By: Relevance
“…Infrequent deviants occurring in a sequence of standard stimuli typically elicit the MMN wave. Previous studies have shown that more salient stimuli with longer gaps give rise to higher amplitudes and shorter latencies [9][10][11][12][13]. In those studies, both gap duration and perceptual accuracy were confounded, making it difficult to determine whether the increase in MMN amplitude with gap size reflected gap duration per se or perceptual saliency.…”
Section: Introductionmentioning
confidence: 87%
“…Infrequent deviants occurring in a sequence of standard stimuli typically elicit the MMN wave. Previous studies have shown that more salient stimuli with longer gaps give rise to higher amplitudes and shorter latencies [9][10][11][12][13]. In those studies, both gap duration and perceptual accuracy were confounded, making it difficult to determine whether the increase in MMN amplitude with gap size reflected gap duration per se or perceptual saliency.…”
Section: Introductionmentioning
confidence: 87%
“…Applying this to the present findings, recall that reverberation and short WDRC release times cause additive distortion to the temporal envelope of a speech signal (Reinhart et al, 2016). In addition, age and hearing loss already require compensatory top-down processing of speech (Alain, McDonald, Ostroff, & Schneider, 2004;Pichora-Fuller, Schneider, & Daneman, 1995). Thus, it may be that the additional distortion introduced by short WDRC release times overloads the cognitive compensation mechanism (i.e., task demand surpasses available cognitive resources) when listeners are already being taxed by aging, hearing loss, and reverberation.…”
Section: Discussionmentioning
confidence: 99%
“…This effect, however, is reduced when older participants are instructed to actively attend to the temporal structure of the auditory presentations. Alain and colleagues showed that while automatic central auditory processing may be reduced in older adults (Alain, McDonald, Ostroff, & Schneider, 2004;for review: Alain, Dyson, & Snyder, 2006), older adults are as sensitive as young adults to near-threshold deviance gaps during active listening conditions.…”
Section: Visual Dominancementioning
confidence: 99%